Effect of Perceived Social Support on Psychache: Mediating Effect of Psychological Resilience - Ling Zhang; Jinxia Pang; Fangli Zhu (Tehran University of Medical Sciences, 2022)
Background: As education develops, it proposes increasing requirements on the quality of teachers. Thus, attention on the mental health problems of teachers has also been gaining increasing attention. However, specific studies on the relationship among teachers' perceived social support, psychache, and psychological resilience remain lacking. Methods: Overall, 430 teachers (including teachers from universities, middle schools, and primary schools) from Zhejiang, Shanghai, Anhui, Hubei, Shanxi, Guangxi and other provinces in China were investigated in 2021 by using perceived social support scale, psychache scale, and psychological resilience scale. Results: Teachers' perceived social support is below the average, whereas psychache and psychological resilience are above the average. A significant gender difference exists in teachers' psychache, and female teachers showed significantly higher teachers' psychache than male teachers (P<0.05). Teachers' psychache showed significantly negative correlations with perceived social support (r=−0.465, P<0.01) and psychological resilience (r=−0.526, P<0.01), but teachers psychological resilience had a significantly positive correlation with perceived social support (r=0.439, P<0.01). Teachers' perceived social support (β=−0.465, P<0.01) could make a negative significant prediction of teachers' psychache, and teachers' perceived social support (β=0.435, P<0.01) could make a positive significant prediction of teachers' psychological resilience. Moreover, psychological resilience had partial mediating effect between perceived social support and psychache, which accounts for 37.6% of the total effect. Conclusion: Perceived social support not only is an important factor that influences teachers' psychache directly but can also influence the psychache of teachers indirectly through psychological resilience.